Tibiotalokalkaneální artrodéza: srovnání metod fixace, střednědobé klinické výsledky - Rapi, Jakub; Nachtnebl, Luboš; Mahdal, Michal; Apostolopoulos, Vasileios; Liskay, Jakub; Tomáš, Tomáš (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY The authors focused on the topic of tibiotalocalcaneal arthrodesis. It is a surgical procedure used to manage severe comprehensive ankle and hindfoot pathology. The scope of surgery and the negative impact on the walking stereotype are offset by preserving a weight-bearing and pain-free limb. The purpose of the study was to evaluate the group of patients who had undergone surgery at the First Department of Orthopaedic Surgery, St. Anne s University Hospital Brno and to identify the most suitable fixation for arthrodesis. It also aimed to compare the outcomes achieved by the authors with those reported by other departments. MATERIAL AND METHODS The group included patients operated on at the authors department between 2011 and 2021. The surgery was indicated in patients with severe concomitant arthritis of the upper and lower ankle, complex hindfoot instability, Charcot arthropathy. Contraindications included acute infection, decompensated diabetes and heavy smoking. The study compares fixation using a lateral plate, a retrograde nail and a retrograde nail with fibula acting as biological plate. The patients were scored preoperatively and postoperatively using the AOFAS Ankle-Hindfoot Score. Statistical analysis of the results was also carried out. RESULTS The group included 23 patients, of whom a lateral plate was opted for in 7 patients, a retrograde nail in 8 patients and a retrograde nail with fibula used as a biological plate in 8 patients. The patients of the group were followed up for the period ranging from 0.5 to 9 years after surgery. Serious complications were observed by the authors in 6 patients of the group. The failure of osteosynthesis material was reported in 2 cases with lateral plating fixation. A stress fracture above the apex of the nail developed in 2 cases. A serious infection was observed by the authors in 1 patient. The method associated with the lowest incidence of complications was the fixation with a retrograde nail and fibula used as a biological plate. DISCUSSION The forms of fixation for tibiotalocalcaneal arthrodesis have recently advanced considerably, the methods of fixation for arthrodesis in particular. The modern implants enable to compress the individual structures, to provide stable fixation and potentially to avoid long-term plaster cast fixation. Nonetheless, these surgical procedures are associated with a high complication rate. Currently, there is no consensus in international studies on the optimal fixation for arthrodesis. Numerous papers describe complications including postoperative infections, failure of osteosynthesis material and fractures close to osteosynthesis material. The number and the type of complications observed by the authors in their group of patients were similar to those reported by other authors. CONCLUSIONS Tibiotalocalcaneal arthrodesis is a surgical procedure reserved exclusively for patients indicated based on strict criteria and should be performed by an experienced team able to cope with potential complications. In the followed-up group of patients, the optimal method of fixation for arthrodesis appeared to be the fixation with a retrograde nail and fibula used as a biological plate. Key words: tibiotalocalcaneal arthrodesis, retrograde nail, lateral ankle plate, ankle instability, ankle arthrosis, biological plate.
Keywords: kostní hřeby; Retrospective Studies; Ankle Joint; lidé; Joint Instability; osteoartróza; výsledek terapie; retrospektivní studie; artrodéza; Humans; Osteoarthritis; Treatment Outcome; nestabilita kloubu; hlezenní kloub; Arthrodesis; Bone Nails